Effect of processing parameters on microstructural properties of lead magnesium niobates. Issue 6 (16th November 2017) - Bhakar, Ashok; Pandey, Adityanarayan H.; Singh, M. N.; Upadhyay, Anuj; Sinha, A. K.; Gupta, S. M.; Ganguli, Tapas; Rai, S. K.
Abstract : Microstructural analysis of the room‐temperature synchrotron X‐ray diffraction (XRD) data of lead magnesium niobate samples prepared under different processing conditions has been carried out using the Rietveld method to study the polar nanoregions ( R 3 m phase). This is the minor phase and normally not accessible at room temperature using laboratory‐source XRD data. It is found that the Gaussian component of size broadening is apposite for the polar rhombohedral phase ( R 3 m ) and the Lorentzian component of strain broadening is apposite for the paraelectric cubic phase ( Pm m ). Abstract : The synchrotron powder X‐ray diffraction (XRD) and subsequent detailed Rietveld analysis of lead magnesium niobate (PMN) samples were performed to study the microstructural properties of polar nanoregions (PNRs) of the R 3 m phase. PMN samples were synthesized under different sample processing conditions. The line profile broadening analysis of room‐temperature synchrotron powder XRD patterns was performed using the multi‐phase Rietveld refinement method for isotropic microstructural evaluation of different PMN samples. The two phases of perovskite PMN considered in the Rietveld refinement approach for satisfactorily fitting the XRD patterns are the paraelectric cubic phase ( Pm m ) and the local rhombohedral phase ( R 3 m ) which corresponds to the PNRs. It is observed that the contributions of the Gaussian component of size broadening of the polar rhombohedral phase ( R 3 m ) and the Lorentzian component of strain broadening of the paraelectric cubic phase ( Pm m ) are apposite for satisfactory Rietveld refinement of the synchrotron XRD data for all PMN samples. The volume‐average crystallite size of PNRs ( R 3 m phase) is almost invariant (approximately 12 nm) with increasing processing temperature while their weight percentage increases. The values of the apparent microstrain in the paraelectric cubic phase ( Pm m ) are larger for hot‐pressed samples.